72.1k views
1 vote
(
((2)/(3) x^(-3) y^(4) z^(2))^(3)

1 Answer

5 votes

\bf ~~~~~~~~~~~~\textit{negative exponents} \\\\ a^(-n) \implies \cfrac{1}{a^n} \qquad \qquad \cfrac{1}{a^n}\implies a^(-n) \qquad \qquad a^n\implies \cfrac{1}{a^(-n)} \\\\ -------------------------------


\bf \left(\cfrac{2}{3}x^(-3)y^4z^2 \right)^3\implies \stackrel{\textit{distributing the exponent}}{\left[\left( \cfrac{2}{3} \right)^3x^{^(-3\cdot 3)}y^(4\cdot 3)z^(2\cdot 3) \right]}\implies \cfrac{2^3}{3^3}x^(-9)y^(12)z^6 \\\\\\ \cfrac{8}{27}\cdot \cfrac{1}{x^9}y^(12)z^6\implies \cfrac{8y^(12)z^6}{27x^9}
User Hamdog
by
5.9k points